The Impact of Physical Activity on Gut Microbiota: An In-Depth Literature Review - Palacz, Karolina Alicja; Lenartowicz, Iwona; Brzozowska, Patrycja; Frańczuk, Agata; Nowińska, Bianka; Makłowicz, Aleksandra (Quality in Sport, 2024)
Introduction. The human body is home to a diverse community of microorganisms known as the microbiota. These microorganisms, including bacteria, fungi, and viruses, play crucial roles in maintaining overall health. They colonize the digestive tract shortly after birth, and the composition of the gut microbiota changes throughout an individual’s life, largely influenced by diet and physical activity. Breastfeeding has long-term beneficial effects on the gut microbiota and gene expression in intestinal cells. Regular exercise not only improves cardiovascular and respiratory health but also affects metabolic, immunological, neural, and microbial pathways. This review explores how diet and physical activity impact the composition and diversity of gut microbiota, highlighting important findings and their implications for health. Aim of study. This study aims to review how physical activity influences gut microbiota, investigating the effects of different types and intensities of exercise on microbial composition and diversity, and their implications for overall health. Materials and methods. A non-systematic examination of the scientific literature was conducted using specific keywords such as gut microbiota, physical activity, sport, and microbiome. The examination took place on PubMed, with scrutiny of a total of 31 references published up to 2023. Conclusions. This review highlights the crucial role of gut microbiota in maintaining good health and its complex interaction with diet and physical activity. Regular exercise has a positive impact on the diversity of microbiota, especially when started at a young age. Imbalance in gut bacteria is linked to various diseases, underscoring the significance of a healthy microbiome. Encouraging physical activity and a nutritious diet can improve gut health, and more research is needed to understand the mechanisms and potential health indicators involved.